The transcriptional basis of chromosome pairing. - Cook, P (1997)
Pairing between homologous chromosomes is essential for successful meiosis; generally only paired homologs recombine and segregate correctly into haploid germ cells. Homologs also pair in some somatic cells (e.g. in diploid and polytene cells of Drosophila). How homologs find their partners is a mystery. First, I review some explanations of how they might do so; most involve base-pairing (i.e. DNA-DNA) interactions. Then I discuss the remarkable fact that chromosomes only pair when they are transcriptionally active. Finally, I present a general model for pairing based upon the DNA-protein interactions involved in transcription. Each chromosome in the haploid set has a unique array of transcription units strung along its length. Therefore, each chromatin fibre will be folded into a unique array of loops associated with clusters of polymerases and transcription factors; only homologs share similar arrays. As these loops and clusters, or transcription factories, move continually, they make and break contact with others. Correct pairing would be nucleated when a promoter in a loop tethered to one factory binds to a homologous polymerizing site in another factory, before transcription stabilizes the association. This increases the chances that adjacent promoters will bind to their homologs, so that chromosomes eventually become zipped together with their partners. Pairing is then the inevitable consequence of transcription of partially-condensed chromosomes.